Morphology and histology of silent and symptom-causing atherosclerotic carotid plaques – Rationale and design of the Helsinki Carotid Endarterectomy Study 2 (the HeCES2). (18th August 2018) - Nuotio, Krista; Ijäs, Petra; Heikkilä, Hanna M.; Koskinen, Suvi M.; Saksi, Jani; Vikatmaa, Pirkka; Sorto, Pia; Mäkitie, Laura; Eriksson, Henrietta; Kasari, Sonja; Silvennoinen, Heli; Valanne, Leena; et al.
Abstract: Introduction : Every fifth ischemic stroke is caused by thromboembolism originating from an atherosclerotic carotid artery plaque. While prevention is the most cost-effective stroke therapy, antiplatelet and cholesterol-lowering drugs have a ceiling effect in their efficacy. Therefore, discovery of novel pathophysiologic targets are needed to improve the primary and secondary prevention of stroke. This article provides a detailed study design and protocol of HeCES2, an observational prospective cohort study with the objective to investigate the pathophysiology of carotid atherosclerosis. Materials and Methods : Recruitment and carotid endarterectomies of the study patients with carotid atherosclerosis were performed from October 2012 to September 2015. After brain and carotid artery imaging, endarterectomised carotid plaques (CPs) and blood samples were collected from 500 patients for detailed biochemical and molecular analyses. Findings to date : We developed a morphological grading for macroscopic characteristics within CPs. The dominant macroscopic CP characteristics were: smoothness 62%, ulceration 61%, intraplaque hemorrhage 60%, atheromatous gruel 59%, luminal coral-type calcification 34%, abundant (44%) and moderate (39%) intramural calcification, and symptom-causing "hot spot" area 53%. Future plans : By combining clinically oriented and basic biomedical research, this large-scale study attempts to untangle the pathophysiological perplexities of human carotid atherosclerosis. Key Messages: This article is a rationale and design of the HeCES2 study that is an observational prospective cohort study with the objective to investigate the pathophysiology of carotid atherosclerosis. The HeCES2 study strives to develop diagnostic algorithms including radiologic imaging to identify carotid atherosclerosis patients who warrant surgical treatment. In addition, the study aims at finding out new tools for clinical risk stratification as well as novel molecular targets for drug development.